Prototyping through the Lens of Network Analysis and Visualisation. (May 2022) - Kent, L.; Gopsill, J.; Giunta, L.; Goudswaard, M.; Snider, C.; Hicks, B.
Abstract: Prototyping is a well-established and valued design process activity. However, capturing prototypes and the tacit knowledge that led to and was gained from their creation is a challenge. Beyond that, questions remain on how best to utilise that captured data. This paper looks at how one can exploit and generate insights from data that has been captured, specifically looking at graph databases, the network analysis techniques they permit and the differing fidelities of visualisation and interactivity that they enable.